The Unified Protocol for Transdiagnostic Treatment of Emotional Disorders Among Japanese Children: A Pilot Study - Fujisato, Hiroko; Kato, Noriko; Namatame, Hikari; Ito, Masaya; Usami, Masahide; Nomura, Tomoko; Ninomiya, Shuzo; Horikoshi, Masaru (Frontiers in Psychology, 2021)
At present, there is no established cognitive behavioral therapy for treating emotional disorders in Japanese children. Therefore, we introduced the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in Children (UP-C) in Japan and adapted it to the Japanese context. We then examined its feasibility and preliminary efficacy using a single-arm pretest, posttest, follow-up design. Seventeen Japanese children aged between 8 and 12 years (female n = 11; male n = 6; M = 10.06 ± 0.97 years) with a principal diagnosis of anxiety, obsessive-compulsive, or depressive disorders, and their parents were enrolled in the study. The primary outcome was the overall severity of emotional disorders as assessed by psychiatrists using the Clinical Global Impression-Severity Scale. Secondary outcomes included child- and parent-reported anxiety symptoms, depressive symptoms, and functional status. No severe adverse events were observed. The feasibility was confirmed by the low dropout proportion (11.76%), high attendance proportion (children: 95.6%; parents: 94.6%), and sufficient participant satisfaction. Linear mixed models showed that the overall severity of emotional disorders and child- and parent-reported anxiety symptoms improved from pre-treatment to post-treatment, and that these treatment effects were maintained during the 3-month follow-up period. Additionally, child- and parent-reported functional status improved from pre-treatment to the 3-month follow-up. In contrast, child-reported depressive symptoms improved from pre-treatment to follow-up, but there was no significant change in parent-reported depressive symptoms between pre-treatment and other time points. These findings demonstrate the feasibility and preliminary efficacy of the Japanese version of the UP-C, suggesting that future randomized controlled trials are warranted (Clinical trial registration: UMIN000026911).